Saranghaeyo Indonesia: Educational Values, Identity and Languange Preference of Diaspora on Instagram - Lestari, Yuli Ika; Purnomo, Antonius R. Pujo (Jurnal Pendidikan Edutama, 2024)
This study focuses on how diaspora show the language practices to build identity, and reflect their educational values in the frame of parenting practices which observed in Instagram. Specifically, two Instagram accounts, @bykikidea and @yooliyaeka were examined. The case study designed to explore the phenomenon, by observing these accounts into two main elements: the context and the content of the posts in Instagram. The exploration of content primarily involved identifying visual and descriptive elements in the Instagram posts of both accounts. The context of language practice focused on understanding the preferences and variations in language usage. The study's findings revealed that the language practice content in the @bykikidea and @yooliyaeka accounts represents Javanese-Indonesia, and Korean cultural identity. The descriptive elements of language indicate the use of a mixture of language of the posts. The context of language practice observed through various themes such as food and culinary activities, pregnancy, family clothing style, infant care practices, early educational activities, and celebration of national holidays or religious celebration. Additionally, the findings suggest the emerge of educational values  through the content and the context of post, such as (1) tolerance, (2) respecting others and  (3) critical  thinking. Those values enriched and strengthen their values of parenting practice.